2013
DOI: 10.1016/j.ultsonch.2012.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Green ultrasound-assisted extraction of carotenoids based on the bio-refinery concept using sunflower oil as an alternative solvent

Abstract: A green, inexpensive and easy-to-use method for carotenoids extraction from fresh carrots assisted by ultrasound was designed in this work. Sunflower oil was applied as a substitute to organic solvents in this green ultrasound-assisted extraction (UAE): a process which is in line with green extraction and bio-refinery concepts. The processing procedure of this original UAE was first compared with conventional solvent extraction (CSE) using hexane as solvent. Moreover, the UAE optimal conditions for the subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(124 citation statements)
references
References 20 publications
5
112
1
6
Order By: Relevance
“…The enhancement in extraction obtained by using ultrasound is mainly attributed to the acceleration of the mass transfer as a result of the acoustic cavitations produced in the solvent by the passage of an ultrasound wave. Ultrasound allows greater penetration of solvent into the sample matrix by disrupting the plant cell wall and facilitating the solvent access to the cell content and the release of the extractable compounds (Li et al, 2013). Microwaveassisted extraction determines a faster heating and accelerates the extraction process for adsorption and desorption of the targeted compounds from the matrix (Lianfu and Zelong, 2008).…”
Section: Carotenoid Contents Of the Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhancement in extraction obtained by using ultrasound is mainly attributed to the acceleration of the mass transfer as a result of the acoustic cavitations produced in the solvent by the passage of an ultrasound wave. Ultrasound allows greater penetration of solvent into the sample matrix by disrupting the plant cell wall and facilitating the solvent access to the cell content and the release of the extractable compounds (Li et al, 2013). Microwaveassisted extraction determines a faster heating and accelerates the extraction process for adsorption and desorption of the targeted compounds from the matrix (Lianfu and Zelong, 2008).…”
Section: Carotenoid Contents Of the Oilsmentioning
confidence: 99%
“…Benakmoum et al, (2008) proposed to enrich refined olive oil and refined sunflower oil with carotenoids and lycopene from tomato peels or tomato puree in order to increase the thermal stability of these oils. Sunflower oil was applied as a substitute for organic solvents in a green ultrasound-assisted extraction of carotenoids from fresh carrots (Li et al, 2013) while Zuorro et al, (2013) produced a lycopene-enriched oil by incorporating a tomato oleoresin derived from tomato peels in oil obtained by cold pressing of the tomato seeds.…”
Section: Introductionmentioning
confidence: 99%
“…F values of Y1 and Y2 were calculated to be 25.95 and 50.34, both leading to a P value < 0.0001, suggesting that both the models were statistically extremely significant. The models' coefficient of determination (R 2 ) were 0.9604 and 0.9792, indicating that more than 96.04% and 97.92% of the response variability is explained, and supporting a good accuracy and ability of the established model within the range limits used [48]. Correlation coefficients of 0.9800 and 0.9898 also indicate a good positive correlation between the actual data and the predicted values obtained using CCD.…”
Section: Statistical Analysis and Model Fittingmentioning
confidence: 61%
“…Therefore, in the last years, the search for more sustainable and environment-friendly extraction methods, and following the principles of green chemistry, green extractions processes have become in an important research focus (Chemat et al, 2017). For this reason, alternative technologies such as UAE are being investigated and considered as a green extraction method (Li et al, 2013). Some studies have been shown that UAE reduce the use of extraction solvents, processing time, and therefore, energy consumption enhancing during the extraction of the desired biocomponents (Chemat et al, 2011;Li et al, 2013;Chemat et al, 2017;Jacotet-Navarro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%